Management of Zakat Muqayyad to Students Reviewed from Jasser Auda's Theory of Maqasid Syariah - Rizky Fadhilah; Dhiauddin Tanjung; Hasan Matsum (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to explain the management of muqayyad zakat carried out by the Rumah Zakat institution in Medan. This research is a juridical-empirical or field research. The data sources for this study consist of primary and secondary data, which were collected through observational studies, interviews, and documentation. Once accumulated, the data were analyzed using a qualitative descriptive analysis method. This study aims to explore the management of muqayyad zakat carried out by the Rumah Zakat institution in Medan, examine the system for determining the amount of muqayyad zakat, and understand how the distribution of muqayyad zakat is governed by Islamic law based on the Maqasid Syariah framework by Jasser Auda. After conducting the research, the researcher found several results as follows: The management of muqayyad zakat at Rumah Zakat Medan, in terms of zakat collection, is specifically carried out by amil who serve as fundraisers, receiving contributions from partners and donors. In the distribution process, zakat funds are directly transferred to the parents of students and used as educational funds for the children. Utilizing muqayyad zakat is carried out by organizing educational activities such as Quran learning, surah memorization, and prayer practice. The muqayyad zakat fund for students in Medan does not have a fixed nominal amount, as the amount is determined based on the capability of the partner who provides the muqayyad zakat. The distribution of muqayyad zakat to students is in line with the objectives of Islamic law, as viewed from Jasser Auda's Maqasid Syariah theory, which includes the preservation of intellect ('aql), wealth (mal), and religion (din).